Discourse, More Discourse! (Proceedings of Southern Federal University. Philology, 2017)
Lara N. Sinelnikova (Yalta, Crimea Republic, Russian Federation)The article is an analytical review of three volumes of the Bulletin of the Russian University of Friendship of Peoples on the problem of discourse. The author has formed a number of headings, the complex of which allows to judge the priority areas of modern scientific knowledge, an essential part of which is discourse. The heading «Pragmatics and metapragmatics of discourse» was formed mainly on the basis of the articles of famous foreign researchers. In each article there are curious ideas, and the generalization of the thesis can be as follows: the evaluation category has a direct relation to the pragmatics, and the estimated semantics of the word is manifested in communication. In the section «Synchronization of paradigmatic relations: text, discourse, style, utterance, speech act, genre» the articles are presented, the material of which is important for revealing the paradigmatic relations between the phenomena named in the heading, including the culturally conditioned features. In the heading “Institutional discourses and problems of hybridization of discourses”, the material of articles of both Russian and foreign researchers is summarized, which makes it possible to identify both the general (even universal) orientation of discourse studies and specific approaches and characteristics due to the peculiarities of social processes and national cultural codes . The heading «Identity in its relation to the language / discursive personality» focuses on understanding the close relationship of the category of identity with the problems of discourse and various types of communication.Many authors of the articles present a retrospective of the development of the concepts under consideration, describe the path of their development from the moment they enter the scientific space to the present. At the same time, ways of coordination and integration of methods and approaches are outlined, which is necessary for understanding the prospects of discourse studies.Key words: discourse, discourse study, discurse semantics, pragmatics, metapragmatics, identity, linguistic personality, discursive personality.DOI 10.23683/1995-0640-2017-3-137-152